The Integration of Process-Genre Approach with Project Ibunka in an EFL Writing Class: Students’ Writing Ability - Salsabila, Vinaaini; Maolida, Elis Homsini (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2019)
Process-Genre is Process based approach synthesized with Genre based writing. Meanwhile, Project Ibunka is an online collaborative writing project in which the students from various cultures and countries interact to exchange the ideas in the form of essay writings. This study describes students’ writing ability as the result of the integration of process-genre approach with Project Ibunka in an EFL writing class. It is a case study that involves 46 university students who learn to compose English writing. This study reveals the increase of students’ writing ability indicated by students’ good control of schematic structure and recognition of grammatical features. However, the students face several obstacles in constructing good grammatical sentences.